Risk analysis of water scarcity in artificial woodlands of semi-arid and arid China. (April 2017) - Zhang, Junze; Ding, Zhaowei; Luo, Mengting
Graphical abstract: Differences in the water cost ( W ) and the ecological service value (ESV) of artificial woodlands in China's arid and semi-arid regions. Highlights: A water scarcity endangers artificial woodlands in China's semi-arid and arid areas. The cost of this risk was 5174 RMB ha −1 in 2014 (17% of the ecosystem service value). The long-term benefits and risks are both considerable during ecological restoration. The optimal approach requires collaboration among stakeholders to identify all risks. Abstract: All activities are inherently risky, including seemingly beneficial activities such as ecological restoration. However, small risks are easy to ignore, even if they may accumulate to create a large cumulative risk. Therefore, the long-term ecological benefits and risks of any ecological restoration project must both be considered. However, quantitative evaluation of the risk of afforestation in arid and semi-arid regions has been insufficiently studied. Here, we present a method for evaluating the risk associated with ecological restoration, using water shortages in artificial woodlands in China's arid and semi-arid regions as an example of cumulative risk. We found an annual risk that amounted to 5174 RMB ha −1 in 2014, which was 17% of the ecological service value of the forests. However, this cost depends on changes in the price, availability, and use of water in these regions. If ecological degradation occurs, it will trigger a series of serious consequences, and its cost may far exceed the expected benefits. Our inability to predict natural disasters such as drought and the problem of imperfect communication among stakeholders must be considered to achieve ecological restoration. The method described in this paper will provide theoretical support for future risk evaluations and guidance for the allocation of natural resources such as water, thereby increasing the likelihood of successful environmental management.